PENDIDIKAN KARAKTER SEBAGAI UPAYA PREVENTIF TERHADAP BULLYING PADA SISWA SD - Sangadji, Harina (Program Studi Pendidikan Ekonomi Institut Sain dan Kependidikan (ISDIK) Kie Raha Maluku Utara, 2025)
psychological and social development. Although various anti-bullying programs have been implemented, effective preventive efforts are still a challenge. This study aims to analyze the role of character education as a preventive strategy against bullying in elementary school students in Ternate City. The method used is qualitative research with a case study approach, involving in-depth interviews, participatory observation, and documentation in an elementary school that has implemented a systematic character education program. The results of the study indicate that character education, which includes values ​​such as empathy, tolerance, and social responsibility, has succeeded in reducing bullying behavior in schools. In addition, the implementation of this program also strengthens social relationships between students and forms a more inclusive school climate. The implications of this study are the importance of integrating character education into school policies and the need for parental and community involvement in supporting bullying prevention efforts. Character education is expected to be a more holistic and sustainable approach in creating a safe school environment and supporting optimal student development.